Naming the sites of the opioid crisis in Boston: a political issue - Elsa Vivant (EchoGéo)
This paper analyses the various toponyms of an open drug use scene in Boston, located at the interface of three neighbourhoods – Newmarket, Dudley-Roxbury, and South End, – with diverse uses and dynamics. The reactions and demands of the residents of these different neighbourhoods reveal the power dynamics in the urban space, the toponymic choices of which are the main focus of this analysis: Mass & Cass refers to the urban, colonial and racial history of the city and prohibition; Methadone Mile brings to mind the stigmatization of users and places of care; Recovery Road expresses the emergence of new care and harm reduction practices at work in this sector. Entering this scene by way of these names helps to unravel the complexity of the opioid crisis currently underway in the USA, the political stakes involved, and the changes it is driving in drug policy.